Rapid alloy design from superior eutectic high-entropy alloys - Wu, Qingfeng; Jia, Yuhao; Wang, Zhijun; He, Feng; Wei, Yufan; Li, Junjie; Wang, Jincheng (Scripta materialia, 2022)
The large amounts of data in eutectic high-entropy alloys (EHEAs) provide the opportunity for a rapid design of superior high-entropy alloys (HEAs). In this letter, we proposed a strategy to screen high-performance supersaturated HEAs based on the existing EHEAs with superior properties. The designed HEAs of supersaturated terminal solid solutions possess unique characteristics. On the one hand, the as-cast alloys exhibited primary single-phase dendrites/grains with maximum solid solution hardening and minor interdendritic/intergranular second phases as modifiers. On the other hand, the maximum saturation enabled the highest volume fraction of precipitates during aging. Taking advantage of these characteristics, high strength and ductility were achieved in the designed HEAs. These findings can accelerate the exploration of supersaturated HEAs with superior properties. [Display omitted]